Purification and characterization of malonyl-coenzyme A: 21-hydroxypregnane 21-O-malonyltransferase (Dp21MaT) from leaves of Digitalis purpurea L. - Kuate, Serge Philibert; Maia de Pádua, Rodrigo; Eisenbeiß, Wilhelm Friedrich; Kreis, Wolfgang (Phytochemistry, 2008)
With respect to the cardenolide pathway and the characterization of enzymes involved in the formation of cardenolides, a malonyltransferase, termed malonyl-coenzyme A: 21-hydroxypregnane 21-O-malonyltransferase (Dp21MaT) has been purified. The enzyme catalyses the transfer of the malonyl moiety from malonyl-coenzyme A to 21-hydroxypregnane substrates. Malonyltransferase activity was checked in several potential starting materials including fresh leaves and cell suspension cultures from different plants. Fresh Digitalis purpurea L. leaves turned out to be the best enzyme source. The purification protocol included ammonium sulphate precipitation, hydrophobic interaction chromatography on Phenylsepharose 6 FF, ion exchange chromatography on Source 30 Q, affinity chromatography on Cibacron Blue 3GA and gel filtration on Superdex 75. Gel filtration and native SDS-PAGE analysis showed that Dp21MaT exists as a monomer with a molecular mass of 27 kDa. Its pI, as determined by isoelectric focusing, was 4.66. The enzyme showed maximal activity at pH 6.5 when incubated at 42 °C. The energy of activation was 29.28 kJ mol-1, whereas that of inactivation was 48.57 kJ mol-1. Dp21MaT was purified 252-fold with a yield of about 1%. Hanes plots of kinetic data indicated Km values of 99 μM (Vmax 47.57 μkat kg-1) and 28.44 μM (Vmax 39.4 μkat kg-1 protein) for 3β-benzoyloxy-5β-pregnane-14β,21-dihydroxy-20-one and malonyl-CoA, respectively. © 2007 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2008.nat.dbio.LPB.purifi
Keywords: 21-Hydroxypregnane 21-O-malonyltransferase; 21-O-Hydroxypregnanes; Cardenolides; Cardiac glycosides; Digitalis purpurea; Enzyme purification; Malonyl-coenzyme A; Plantaginaceae